(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the pervasive themes of domestic violence and rape in Alice Walker’s The Color Purple through the lens of [post]postmodern literary critique. It examines how the novel’s narrative structure, character arcs, and linguistic experimentation contribute to a profound critique of patriarchal violence and its intersections with race, gender, and class. By integrating postmodern and post-postmodern methodologies, this study highlights the fragmented subjectivities and intergenerational trauma experienced by the characters while acknowledging the transformative potential of resilience, agency, and community. This analysis seeks to illuminate Walker’s radical narrative strategies, her depiction of intersectional oppression, and the overarching redemptive arcs that redefine survival and empowerment in a fractured world.